Main Problems in Islamic Education - Sitti Maulida (STIT Attaqwa, 2024)
This paper discusses the main problems in Islamic education, which of these problems can hinder the continuity of Islamic education. In this paper will discuss several problems ranging from basic problems that often occur, structural problems or structural problems, operational problems or operational problems, vision and mission problems that are problems related to the vision and mission of Islamic education, epistemological problems of Islamic education are more directed at methods or approaches that can be used to build Islamic science, Both conceptually and applicatively, science and technology problems are problems related to the rapid development of science and technology, and the last is the problem of normative-deductive thinking traditions.